Spent Bleaching Earth sebagai Adsorben untuk Menyisihkan Krom dan Warna pada Limbah Cair Batik - Ferlian Vida Satriaji; Novirina Hendrasarie (Jurnal Serambi Engineering, 2024)
Environmental pollution by heavy metals, including chromium, is a common issue, particularly in the batik industry. Chromium, although essential, can become a hazardous substance in its +6-oxidation state. This research aims to investigate the use of spent bleaching earth as an adsorbent to remove chromium ions (Cr) and color from batik industry wastewater. The study consists of two main phases: a preliminary study and the main research phase. In the preliminary phase, the initial characteristics of batik wastewater were tested, and a coagulation-flocculation-sedimentation process was performed to reduce parameters that could interfere with the adsorption process. The primary adsorbent material used was spent bleaching earth, with a comparative adsorbent consisting of pure bleaching earth and powdered activated carbon. In the main research phase, the treated wastewater was flowed into an adsorption reactor. Variables varied included flow rate (7 mL/minute and 15 mL/minute) and adsorbent mass (30 grams and 50 grams). The analysis revealed that lower flow rates and greater adsorbent masses increased adsorption efficiency. Adsorption capacity was calculated using the Thomas mathematical model. Spent Bleaching Earth proved to be effective in adsorbing chromium ions (Cr) and color, with an adsorption capacity exceeding 85%.